The Relationship Between Consumer Behavior and Financial Decision-Making in the Shopee Platform of Job Orders and Regular Government Employees in the City of Mati - Dan Lloyd Ordaneza Dacillo; Liezl Makiling Apeque; Maria Camila Silla Fuertes (Universitas Multi Data Palembang, 2026)
This study examined the relationship between consumer behavior and financial decision-making among 200 Job Order (JO) and Regular Government employees in Mati City who use Shopee. Using stratified and convenience sampling, data were analyzed through descriptive statistics, ANOVA, and Pearson correlation to assess the effects of age, sex, and employment status. Results showed very high levels of both consumer behavior and financial decision-making. Age had no significant effect, while sex influenced customer satisfaction and financial knowledge. Employment status significantly affected purchasing patterns, perceived convenience, customer satisfaction, and financial literacy, underscoring the importance of job security and income stability. A strong positive correlation (r = 0.632) was found between consumer behavior and financial decision-making. The findings highlight the need for targeted financial literacy programs and employment policies that promote financial stability. However, the study’s focus on a single city and use of non-probability sampling limit its generalizability. Future research should involve broader populations and additional variables to deepen understanding.